2013
DOI: 10.1007/s00415-013-7154-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the differences in care for 5,000 Spinal Muscular Atrophy patients, a survey of 24 national registries in North America, Australasia and Europe

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive genetic disorder characterised by the degeneration of motor neurons and progressive muscle weakness. It is caused by homozygous deletions in the survival motor neuron gene on chromosome 5. SMA shows a wide range of clinical severity, with SMA type I patients often dying before 2 years of age, whereas type III patients experience less severe clinical manifestations and can have a normal life span. Here, we describe the design, setup and utilisation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 18 publications
1
70
1
5
Order By: Relevance
“…Globally, however, there are differences regarding the level of ventilatory and nutritional support provided to patients with SMA type 1 16. We describe transformations in optimal multidisciplinary care accompanying active therapy and increased complexity of clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, however, there are differences regarding the level of ventilatory and nutritional support provided to patients with SMA type 1 16. We describe transformations in optimal multidisciplinary care accompanying active therapy and increased complexity of clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Patient registries, for example, are important tools for collecting phenotypic and natural history data from patients across multiple centres and countries, and in rare disease these have proved to be crucial tools for gaining knowledge about disease progression, survival, care outcomes and response to therapy as well as finding particular subsets of patients for recruitment into clinical trials. Examples include the long-running registries for lysosomal storage diseases such as Fabry, Gaucher and Pompe disease, which have collected extensive clinical data supporting research into these conditions and assessing therapeutic response [43], or the TREAT-NMD registries for DMD [44] and spinal muscular atrophy [45], which have collected data on over 10,000 DMD and 3000 spinal muscular atrophy patients and enabled recruitment into clinical trials. However, the proliferation of registries for individual rare diseases and relative lack of interoperability of datasets means that here, too, harmonisation is required, and this is being addressed by a number of initiatives including RD-Connect and the European Commission itself through its Joint Research Centre in Ispra, Italy [46].…”
Section: Collaboration and Harmonisation Of Efforts In Rare Disease Rmentioning
confidence: 99%
“…Cold-shock suppresses transcription and may also be associated with oxidative stress due to associated changes in reactive oxygen species (Al-Fageeh and Smales, 2006). A large collaborative study analyzed the differences in care for SMA patients in North America, Australasia, and Europe (Bladen et al 2014). Within the data from this study, Tsai et al identified a correlation between climate and SMA type III ambulation, in which regions with cooler climates (Germany/Austria, Switzerland, and the UK) have patients with a more extended period of ambulation than those in countries with warmer climates (Argentina, Hungary, Ukraine, and Serbia) (Tsai et al 2016; Bladen et al 2014).…”
Section: Hypoxic Stressmentioning
confidence: 99%
“…A large collaborative study analyzed the differences in care for SMA patients in North America, Australasia, and Europe (Bladen et al 2014). Within the data from this study, Tsai et al identified a correlation between climate and SMA type III ambulation, in which regions with cooler climates (Germany/Austria, Switzerland, and the UK) have patients with a more extended period of ambulation than those in countries with warmer climates (Argentina, Hungary, Ukraine, and Serbia) (Tsai et al 2016; Bladen et al 2014). The interpretation of this data by Tsai et al did not take into consideration differences in health care systems of these countries or dietary or cultural considerations that may also contribute to the phenotypic severity (Tsai et al 2016).…”
Section: Hypoxic Stressmentioning
confidence: 99%